Inhibitory effect of Lactobacillus rhamnosus on pathogenic bacteria isolated from women with bacterial vaginosis - Eslami, Gita; Taheri, Sudabeh; Azargashb, Eznollah; karimiravesh, raheleh (Novelty in Biomedicine, 2014)
Background: Considering the high prevalence of bacterial vaginosis and its association with urinary tract infection in women and treatment of gynecologic problems occur when a high recurrence of bacterial vaginosis is often treated with antibiotics. The purpose of this study is to investigate the inhibitory effect of Lactobacillus rhamnosus on pathogenic bacteria isolated from women with bacterial vaginosis, respectively. Materials and Methods: 96 samples from women with bacterial vaginosis discharge referred to health centers dependent Shahid Beheshti University in 91-92 were taken by a gynecologist with a dacron swab and put in sterile tubes containing TSB broth and Thioglycollate broth and were immediately sent to the lab location in cold chain for the next stages of investigation. From Thioglycollate and TSB medium was cultured on blood agar and EMB and Palkam and Differential diagnosis environments, and then incubated for 24 h at 37°C. Strains of Lactobacillus rhamnosus were cultured in MRSA environment and were transfered to the lab. After purification of pathogenic bacteria, MIC methods and antibiogram, Lactobacillus rhamnosus inhibitory effect on pathogenic bacteria is checked. Statistical analysis was done by SPSS software v.16. Results: The results of this study show the inhibitory effect of Lactobacillus rhamnosus on some pathogenic bacteria that cause bacterial vaginosis, including Staphylococcus aureus, Staphylococcus epidermidis, Staphylococcus saprophyticus, Streptococcus agalactiae, Entrococcus, Listeria monocytogenes and E.Coli. Microscopic examination of stained smears of the large number of Lactobacillus and pathogenic bacteria showed reduced. The prevalence of abnormal vaginal discharge, history of drug use means of preventing pregnancy and douching, respectively, 61%, 55%, 42% and 13% respectively. Significant difference was observed between the use and non-use of IUD in women with bacterial vaginosis infection. Conclusion: Our findings indicated the Inhibitory effect of Lactobacillus rhamnosus on the pathogenic bacteria that cause bacterial vaginosis. The results of this study confirm the hypothesis of inhibit of pathogens growth that cause bacterial vaginosis supported by probiotics and can have beneficial effects in the prevention and treatment of bacterial vaginosis.